Cost Effectiveness of CABG Versus PCI for Patients With Coronary Artery Disease: A Systematic Review - Trias Roslina; Prastuti Soewondo (Eduvest - Journal of Universal Studies, 2024)
The suitability of CABG compared to PCI for patients with coronary artery disease (CAD) remains a controversial issue. Despite growing evidence supporting the clinical efficacy of these revascularization strategies, there is little evidence regarding their long-term cost-effectiveness. The aim of this study was to critically evaluate the literature regarding the cost-effectiveness of CABG compared to PCI and assess the quality of the available economic evidence.The methods is a systematic review was conducted using three databases: PubMed, Scopus and Google Scholar. Three studies were retrieved then compared the economic evaluation of CABG vs PCI measures The result is the improvement (ICER) reported across studies varied widely by perspective and timeframe. ICER calculation was reported to be favorable and cost effective for CABG. The conclusions is CABG is more cost-effective than PCI in cases of coronary artery disease. The evidence supporting this cost-effectiveness will continue to evolve and further evaluation over a period of 10 years or more is needed considering societal perspectives.